Pengaruh Intensitas Penggunaan Media Sosial Tiktok terhadap Preferensi Gaya Makeup di Kalangan Siswi SMA Sulthon Aulia Boarding School Bekasi - Firdausi, Keysha Farina; Hidayah, Nurul; Atmanto, Dwi (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the influence of Tiktok social media usage intensity on makeup style preferences among female students at Sulthon Aulia Boarding School Bekasi. In today’s digital era, Tiktok has become a highly influential platform in shaping beauty trends, especially among teenagers, including in the use of makeup. This research uses a quantitive approach with a survey method and simple linear regression analysis. A total of 61 students were selected through purposive sampling. The research instrument was a Likert scale-based questionnaire. The correlation test results show a very strong relationship between Tiktok usage intensity and makeup style preference (r = 0,870). The t-test results show a significance value of 0,000 (<0,05), indicating a significant effect between the two variables. Thus, it can be concluded that the higher the intensity of Tiktok usage, the greater the tendency of students to follow certain popular makeup trends on the platform. These findings are expected to serve as a reference for school and parents in guiding responsible social media usage.